Application of Amorphous Alloy Co69Nb25B6 for Orthopedic Implants - Nascimento, Luciano; Souza, José William de Lima; Silva, Suédina Maria de Lima; de Melo Costa, Ana Cristina Figueiredo (Orbital: The Electronic Journal of Chemistry, 2025)
This study investigates the potential of the amorphous alloy Co69Nb25B6 as a promising biomaterial for orthopedic implants. The alloy was produced via high-energy milling (HEM). An amorphous Co69Nb25B6 powdered alloy was prepared by mechanical alloying process. Notably, 20 g of powder were used with a powder-to-ball weight ratio of approximately 20:1 at a rotation speed of 300 rpm. Characterization of the Co₆₉Nb₂₅B₆ alloy was carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), and a vibrating sample magnetometer (VSM). The results showed that the amorphous Co69Nb25B6 alloy powder exhibited a high degree of amorphous phase formation, a flake-like morphology, and a particle size of approximately 10 μm. Additionally, the Co69Nb25B6 alloy demonstrated soft ferromagnetic behavior, with a saturation magnetization of 0.23 emu/g after 20 h of milling. This research highlights the potential of amorphous alloy Co69Nb25B6 as a viable material for traumatic orthopedic medical devices.